Cardiac monitoring in HER2-positive patients on trastuzumab treatment: A review and implications for clinical practice. (August 2020) - Bouwer, Nathalie I.; Jager, Agnes; Liesting, Crista; Kofflard, Marcel J.M.; Brugts, Jasper J.; Kitzen, Jos J.E.M.; Boersma, Eric; Levin, Mark-David
Abstract: Trastuzumab prolongs progression-free and overall survival in patients with human epidermal growth factor receptor 2 (HER2) positive breast cancer. However, trastuzumab treatment is hampered by cardiotoxicity, defined as a left ventricular ejection fraction (LVEF) decline with a reported incidence ranging from 3 to 27% depending on variable factors. Early identification of patients at increased risk of trastuzumab-induced myocardial damage is of great importance to prevent deterioration to irreversible cardiotoxicity. Although current cardiac monitoring with multi gated acquisition (MUGA) scanning and/or conventional 2D-echocardiography (2DE) have a high availability, their reproducibility are modest, and more sensitive and reliable techniques are needed such as 3D-echocardiography (3DE) and speckle tracking echocardiography (STE). But which other diagnostic imaging modalities are available for patients before and during trastuzumab treatment? In addition, what is the optimal frequency and duration of cardiac monitoring? At last, which biomarker monitoring strategies are currently available for the identification of cardiotoxicity in patients treated with trastuzumab? Highlights: Current MUGA is not sensitive and reliable enough to detect cardiotoxicity early. 3DE (with STE) is most suitable for cardiac monitoring of patients on trastuzumab. The optimal frequency and duration of cardiac monitoring is not yet established. MPO and hs-troponin are promising biomarkers to detect cardiotoxicity.